2017
DOI: 10.1353/hpu.2017.0068
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hypertension Management and Outcomes at an Indianapolis Student-Run Free Clinic

Abstract: Despite unfavorable demographic characteristics, records for patients with hypertension who used IUSOC as a regular provider of primary care compared favorably with national data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Treatment outcomes regarding hypertension were the second-most examined after diabetes, with six studies published since 2012. All studies relate to US-based SRCs involving medical school students, with one also including pharmacy students 45 and another pharmacy and nursing students. 42 Five 40 , 41 , 43–45 involved chart review of recorded blood pressure (mmHg) for patients receiving care in a primary care SRC.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment outcomes regarding hypertension were the second-most examined after diabetes, with six studies published since 2012. All studies relate to US-based SRCs involving medical school students, with one also including pharmacy students 45 and another pharmacy and nursing students. 42 Five 40 , 41 , 43–45 involved chart review of recorded blood pressure (mmHg) for patients receiving care in a primary care SRC.…”
Section: Resultsmentioning
confidence: 99%
“…The results for hypertension control differ from other studies on hypertension quality standards at other SRFCs. Smith et al, Wahle et al, and Zucker et al all concluded that the SRFC evaluated was able to improve blood pressure and achieve national quality standards [27][28][29]. The current SRFC literature may be more favorable due to publication bias and the fact that only robust or long-standing SRFCs have the resources to conduct quality-of-care evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…These seem to be common themes in the populations serviced by other SRFCs explored in the literature, allowing these results to be reasonably extrapolated to other clinics. 8,9 Having a pre-defined formulary for the clinic seemed to effectively guide treatment for the patients, as a large proportion of prescriptions filled at the contract pharmacy were adherent to it. In addition, it helps create a controlled learning environment focused on select agents from major pharmacological classes for medical students just learning pharmacotherapy.…”
Section: Descriptive Statisticsmentioning
confidence: 99%